2021
DOI: 10.5194/acp-21-9887-2021
|View full text |Cite
|
Sign up to set email alerts
|

CO<sub>2</sub>-equivalence metrics for surface albedo change based on the radiative forcing concept: a critical review

Abstract: Abstract. Management of Earth's surface albedo is increasingly viewed as an important climate change mitigation strategy both on (Seneviratne et al., 2018) and off (Field et al., 2018; Kravitz et al., 2018) the land. Assessing the impact of a surface albedo change involves employing a measure like radiative forcing (RF) which can be challenging to digest for decision-makers who deal in the currency of CO2-equivalent emissions. As a result, many researchers express albedo change (Δα) RFs in terms of their CO2-e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 96 publications
(131 reference statements)
0
24
0
Order By: Relevance
“…In this study, the shortwave radiative forcing is interpreted as a disturbance of the reflected radiances caused by variations in soil and surface albedos. Therefore, the soil albedo-induced radiative forcing as presented here should not be interpreted as estimates of radiative forcing from different climate forcing agents (Bright & Lund, 2021), but rather as a proxy of the surface shortwave energy imbalance caused by assuming a broadband background soil albedo representation versus a hyperspectral one. The albedo-induced radiative forcing ( 𝐴𝐴 RF𝛼𝛼 𝑠𝑠 ) is given by…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the shortwave radiative forcing is interpreted as a disturbance of the reflected radiances caused by variations in soil and surface albedos. Therefore, the soil albedo-induced radiative forcing as presented here should not be interpreted as estimates of radiative forcing from different climate forcing agents (Bright & Lund, 2021), but rather as a proxy of the surface shortwave energy imbalance caused by assuming a broadband background soil albedo representation versus a hyperspectral one. The albedo-induced radiative forcing ( 𝐴𝐴 RF𝛼𝛼 𝑠𝑠 ) is given by…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the shortwave radiative forcing is interpreted as a disturbance of the reflected radiances caused by variations in soil and surface albedos. Therefore, the soil albedo‐induced radiative forcing as presented here should not be interpreted as estimates of radiative forcing from different climate forcing agents (Bright & Lund, 2021), but rather as a proxy of the surface shortwave energy imbalance caused by assuming a broadband background soil albedo representation versus a hyperspectral one. The albedo‐induced radiative forcing (normalRnormalFαs ${\mathrm{R}\mathrm{F}}_{{\alpha }_{s}}$) is given by RFαs=RTOAΓαnormalΔαs=400normalnm2500normalnmRTOA(λ)Γa(λ)normalΔαs(λ)dλ ${\mathrm{RF}}_{{\alpha }_{s}}=-{R}_{\mathrm{TOA}}^{{\downarrow}}{{\Gamma }}_{\alpha }^{{\updownarrow}}{\Delta }{\alpha }_{s}=\int \nolimits_{400\mathrm{nm}}^{2500\mathrm{nm}}-{R}_{\mathrm{TOA}}^{{\downarrow}}(\lambda ){{\Gamma }}_{a}^{{\updownarrow}}(\lambda ){\Delta }{\alpha }_{s}(\lambda )d\lambda $ where RnormalTnormalOnormalA ${\mathrm{R}}_{\mathrm{T}\mathrm{O}\mathrm{A}}^{{\downarrow}}$ ( λ ) (mW m −2 nm −1 ) is the TOA spectral incoming solar radiation flux following Kurucz (Kurucz, 1992) (Figure S2 in Supporting Information ), Γa ${{\Gamma }}_{\mathrm{a}}^{{\updownarrow}}$( λ ) is the two‐way spectral atmospheric transmissivity that is given as the product of the downward and upward spectral atmospheric transmissivities, assumed to be equal to one another, and ∆ α s ( λ ) is the difference in spectral soil albedo between the hyperspectral and the broadband cases.…”
Section: Resultsmentioning
confidence: 99%
“…where T a is the all-sky monthly mean clearness index and SW ↓ is the incoming shortwave radiation where the subscript m shows the data in month m. A negative RF Δα indicates a cooling effect due to elevated albedo of the forest after a disturbance. T a is a crucial parameter that indicated the atmospheric transmittance of downward shortwave radiation (Chen, 2021), and the square root of Ta is an empirical estimation of transmittance of upward radiative transfer (Bright & Lund, 2021). In this study, T a was calculated as:…”
Section: Calculation Of Radiative Forcing (Rf δα )mentioning
confidence: 99%
“…Another metric, known as time dependent emissions equivalence (TDEE), is more sensitive to changes in the time horizon, and the cumulative value (Σ[TDEE]) can be interpreted as the accumulated CO 2 equivalent within the TH (Bright & Lund, 2021). In this regard, we modeled the potential radiation forcing scenario by using the fit of nonlinear function based on all data points (Section 2.4) to calculate TDEE following Bright and Lund (2021):…”
Section: Radiative Forcing Due To Altered Albedomentioning
confidence: 99%
“…The present scientific understanding of the forcing effects of albedo due to LULCC is ranked as medium-low relative to the rich scientific evidence of the forcing effects of GHGs [1]. To cross-examine effects with the climate impact of other GHGs (i.e., biogeochemical GWI), albedo-induced warming or cooling can be converted into equivalents of carbon-dioxide (CO 2eq ) and/or carbon (C eq ) atmospheric radiative forcing via the concept of albedo-induced global warming potential (GWP ∆α , kg CO 2eq m −2 yr −1 ; [9,10]) metric-hereinafter referred to as global warming impact (GWI ∆α ), to be in line with our previous study [11]. For example, Houspanossian et al [12] found that conversion from forests to croplands, from forests to pastures, and from pastures to croplands in dry subtropical forests of South America offset 12-27 Mg C eq ha −1 during a 12-year period, or from 15% to 55% of the total C emissions due to deforestation.…”
Section: Introductionmentioning
confidence: 99%